Detection and Analysis of the Oral Flora in Patients with Recurrent Aphthous Stomatitis. (13th October 2022) - Cai, Ruolin; Bi, Wei; Yu, Youcheng
Abstract : The present study detected differences in the oral mucosal flora in healthy people and patients diagnosed with recurrent aphthous stomatitis (RAS) using the 16S ribosomal RNA high-throughput sequencing (rRNA-seq). All samples were collected from the lower lip mucosa of 100 healthy individuals and 100 patients with RAS. After the extraction, DNA was subjected to PCR amplification for the bacterial 16S rRNA gene, before subjecting to high-throughput sequencing, and matched to a database. Most bacterial species and most unique bacteria were from the healthy control group, and the amount of operational taxonomic units (OTUs) calculated was similar in the ulcer and nonulcer sites. Firmicutes, Proteobacteria, and Bacteroidetes were most abundant in the healthy group and in ulcer, nonulcer, and healed ulcer sites at the phylum level. Meanwhile, the number of Prevotella was significantly elevated in ulcer sites (P < 0.05 ). Healthy people had more species of bacteria inhabiting their oral mucosa than did RAS patients, and patients with ulcers had the lowest abundance of bacterial species. We suggest that the number of Prevotella is associated with RAS.